Advancements and Future Prospects in Hypocrellins Production and Modification for Photodynamic Therapy - Xiang Zhang; Qiulin Wei; Liwen Tian; Zhixian Huang; Yanbo Tang; Yongdi Wen; Fuqiang Yu; Xiaoxiao Yan; Yunchun Zhao; Zhenqiang Wu; Xiaofei Tian (Fermentation)
Hypocrellins (HYPs), naturally occurring 3,10-xylene-4,9-anthracene derivatives sourced from Shiraia bambusicola and Hypocrella bambusae, exhibit significant photobiological activities. Despite their capability for generating a high yield of reactive oxygen species, including singlet oxygen and superoxide anion radical, their application in photodynamic therapy (PDT) is constrained. This limitation is due to their low dark phototoxicity, weak absorption within the therapeutic window of PDT (600–900 nm), and inherent hydrophobicity, which hinder their immediate use in amphipathic PDT applications. This review comprehensively discusses the research advancements in the bioactivities and biosynthesis of HYPs, alongside the reported chemical and physical modifications that enhance their water solubility and extend their therapeutic window. Additionally, it explores potential strategies for developing pharmaceuticals, photocatalytic agents, and photosensitive pesticides based on HYPs.